Keberkesanan meneroka konsep matematik dengan menggunakan mikrokomputer - Ismail, Zaleha (1992)
This study compared the performance between students who studied calculus by using microcomputer together with attending the traditional lecture and those who studied calculus by attending the traditional lectures only. This study involved 199 students from UTM, ITM and UPM. A microcomputer software caBed 'Exploring Calculus' was used in this study and students' achievement was evaluated to test the effectiveness of this learning technique. The affective aspect on the effects of using microcomputer in learning was also evaluated using a questionnaire. The results of the study showed that the test scores of the students who used microcomputer together with the traditional lecture are higher than those who attended the traditional lecture only. Also, it is found that most students agreed that. using microcomputer is a good teaching method and therefore should be encouraged.